Questioning BPOM: “Which Syrup Medicine is Safe for My Child?” - Nasvian, Moch Fuad; Widiatmojo, Radityo; Daniswara, Airlangga; Ramadhan, Duta (Jogjakarta Communication Conference (JCC), 2023)
The Food and Drug Supervisory Agency (BPOM) credibility is at stake as the Indonesian Pediatric Society and Indonesia’s Health Ministry reported that there was an increase in cases of Acute Kidney Injury in children in 2022. The people and communities consider BPOM to be too slow and is not transparent with this case. As a result, public opinions regarding the case become wilder on social media. This study figures out the interactivity of netizens on the instagram @bpom_ri in the case of Acute Kidney Injury in children. This study uses the thematic analysis and interactivity concept of McMillan. The results of the study showed that the dimension of interactivity in the comments section of BPOM's Instagram posts was high. The highest dimension was the sense of presence. The message relatedness of the comments was mainly linear with the posts. In terms of response, the most common was insight and information. The reactance of emotions showed a mix of positive and negative emotions, with fear being the most prevalent. This study found that netizens have a high willingness to share insight and information to others. They also express emotions such as fear and happiness when discussing medicine and feel connected to other commenters through a sense of presence. Additionally, there is a willingness to participate in a call of action. They keep commenting in BPOM instagram posts even though the comments did not match with the contents. Additionally, the issue of miss-using substances in children's syrup medicine evokes sadness among netizens.